Partnership at Work - Roche, Bill (Routledge Research in Employment Relations, 2006)
The partnership established between the Irish Airports Authority and its trade unions in the mid-1990s was groundbreaking in promoting union and staff involvement in all aspects of company decision-making. This book charts the progress, achievements and obstacles faced by the partnership based on full access to the partners, documents, observations on how the partnership functioned and three surveys of the company's workforce.